Owners’ Valuation of Companion Animals: A Multidimensional Review of the Human-Animal Bond - Kathiravan, G. (International Journal of Bio-resource and Stress Management, 2026)
This review attempted to synthesise these research findings by investigating owners’ perceptions and definitions of the importance of companion animals. Today, pet animals occupy an increasingly central role in human emotional lives. People across cultures no longer regard these creatures as mere means of functioning but as emotionally significant members of households and families. A synthesis across disciplines, this paper reviews literature examining how and why pet owners value their pets, drawing on psychological, sociological, anthropological, public health, and consumer behaviour research. Accordingly, the analysis emphasized that pet value involves several dimensions: emotional attachment, psychological well-being, social support, identity formation, physical health behaviours, and economic investment. Attachment theory, anthropomorphism, and social capital frameworks are intertwined to discuss the dynamics through which owners came to value their pets. Additionally, this review highlighted the importance of considering cultural and contextual differences in pet ownership, as perceptions of pet value could vary across societies and individual life circumstances. Despite a wealth of valid data highlighting positive emotional and social effects of pet ownership, the literature also presented inconsistencies and context-dependent findings, especially with regard to mental and physical health. Future research should aimed to explore longitudinal patterns and cross-cultural comparisons to better understand how these dimensions of pet value evolve over time. Owners’ valuation of pet animals was multidimensional, relational, and socially constructed, the review concluded, and required nuanced interpretation as well as longitudinal and cross-cultural research.